Influence of Wheel Polygonization on Dynamic Response of Gearbox Housing of High-speed Train - ZOU Hangyu; ZHANG Weihua; WANG Zhiwei (机车电传动)
In order to study the dynamic response of gearbox housing of high-speed train under the excitation of polygonal wheel, a vehicle dynamic model including gear transmission systems and gearbox housing finite element model was set up. Line test and modal analysis to gearbox housing were carried out. Acceleration and dynamic stress in the areas cracking initiation prone to begin were analyzed. The result showed that the 20th order polygonal wheel leads to the 1st order resonance of gearbox housing, which results in significant increase of acceleration and stress, with the acceleration and stress of fault condition 4.6 and 45 times larger than normal condition. The influence of wheel polygonization on gearbox housing was local, and the danger areas were around oil sight glass and radiation rib; Fatigue failure was prone to happen when gearbox housing was on abnormal vibration, and the service lifetime of gearbox housing significantly decreased with the increase of the polygon depth. Attention should be paid to danger point in operation and maintenance decision.